Find the fish that looks like this - Wallwork, Amanda (London : Puffin Books, 1994)
Bur you'll have to look closely, because the creatures you'll meet in this book are cleverly hidden. Illustrated with vivid torn-paper collage, this visually stunning book is a treat for puzzle lovers and animal lovers alike.
Keywords: Games-Fiction; Animals-Fiction